(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Which principles of lean manufacturing affect ROE or return on capital? Purpose: The purpose of the research was to carry out a systematic review of empirical research on the principles of lean manufacturing and to check their impact on the return on capital. Method: We used the methods of description and compilation of the results of the considered qualitative and quantitative research. We conducted a systematic review of domestic and foreign empirical research for the past twenty years. The dominant research method used was a combination of quantitative and qualitative methods. Using search terms, we identified 644 scientific works, of which 25 suitable ones were included in the qualitative synthesis. We used the database ProQuest, ScienceDirect, Google scholar, Springer Link, Scopus, Unpaywall, Scientific Research and Scientific & Academic Publishing. We also searched in the repositories of the University of Primorska, the University of Nova Gorica, the University of Ljubljana, the University of Maribor and in the electronic library of the Faculty of Organizational Studies in Novi Mesto. Results: Among the 25 studied scientific works, we found that the authors did not cover all the principles of lean manufacturing in any empirical research. They studied individual principles, and based on this, we cannot say for sure that all principles affect the ROE indicator. However, we identified in the research some principles that influence ROE, namely principle 4 (equalization of the amount of work), principle 5 (TPM), principle 6 (process control), principle 8 (group technology), principle 10 (employee involvement) and principle 11 (communication with suppliers and customer involvement). Most empirical research has been conducted in the field of economic activities. The population covered all forms of business with a large number of respondents, and six were case studies. Surveys were most often used to obtain data, although new manuals, simulations and new models were not lacking. Organization: By presenting the state of research in the field of lean manufacturing principles on return on capital, we present the most frequently discussed lean manufacturing principles to organizations. Based on this, organizations have the opportunity to examine their own situation in this area and identify potential opportunities for improvement. Society: The economy affects the quality of life, and in the case of good business, this impact is even greater. With increasing public interest, organizations also have an increased opportunity to select and acquire personnel suitable for their operations and to continue growing their performance. Originality: The research showed a lack of research in the field of lean manufacturing principles as building blocks of the success of companies. Most of the research to date is based on attempts to introduce these principles, but there has not yet been research into the success of their impact on the return on capital. Limitations/Future Research: The research was limited to 25 scientific works from the period from 2000 to 2022. Based on the identified research proposals or perceived gaps, a quantitative study of the influence of lean manufacturing principles on the performance of medium and large organizations, as measured by the return on capital indicator, would significantly contribute to new knowledge in the field.